Unveiling The Vital Role of Flavonoids in Combating Bad Cholesterol: A Scientific Approach - Arief, Ria Qadariah; W, Linda Prasetyaning; L, Sri Hidayati; Oktorina, Sarita; Firnanda, Bunga Janviera (International Conference on Sustainable Health Promotion, 2023)
Flavonoids are important ingredients found in herbal plants to prevent dyslipidemia. This study aimed to explore the broad potential of flavonoids in suppressing bad cholesterol problems. The type of research conducted is to review articles appropriate to the topic of discussion. The articles we analyze have PICOS criteria, and the process is depicted in a prism diagram. We got 8 articles that discussed the role of flavonoids in limiting the production of bad cholesterol in test animals’ bodies. Flavonoids that are studied are derived from several different types of plants with different dosages and compositional formulas. Hopefully, this research can be a source regarding the important role of flavonoids in cholesterol metabolism in the body